Sewage-sludge-derived carbonaceous materials for catalytic wet hydrogen peroxide oxidation of m-cresol in batch and continuous reactors. Issue 2 (17th January 2016) - Yu, Yang; Wei, Huangzhao; Yu, Li; Wang, Wei; Zhao, Ying; Gu, Bin; Sun, Chenglin
Abstract : In this study, four sewage-sludge-derived carbonaceous materials (SWs) were evaluated for their catalytic wet hydrogen peroxide oxidation (CWPO) performance of m -cresol in batch reactor and continuous reactor, respectively. The SWs were produced by carbonization (SW); carbonization with the addition of CaO (CaO-SW); HNO3 pretreatment (HNO3 -SW) and steam activation (Activated-SW). The properties of SW catalysts were assessed by thermogravimetric analysis, Brunauer–Emmett–Teller, Fourier Transform Infrared Spectroscopy, X-ray Fluorescence, Scanning electron microscopy, energy dispersive X-ray analysis and zeta potential. The results showed that SW treated by HNO3 (HNO3 -SW) had a high conversion of m -cresol in batch reactor and continuous reactor, respectively. Under the conditions of batch reaction (C m -cresol = 100 mg L −1, CH2O2 = 15.7 mmol L −1, initial pH=7.0, 0.5 g L −1 catalyst, 80°C, 180 min adsorption and 210 min oxidation), the conversion of m -cresol reached 100% and total organic carbon removal was 67.1%. It had a high catalytic activity and stability on the treatment of m -cresol in CWPO for more than 1100 h. Furthermore, a possible reaction mechanism for the oxidation of m -cresol to 2-methyl-p-benzoquinone by CWPO was proposed.